PENGUKURAN USABILITY WEBSITE E-COMMERCE SAMBAL NYOSS MENGGUNAKAN METODE SKALA LIKERT - Setyawan, Ryan Ari; Atapukan, Walter F (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2018)
The purpose of this study is to measure the usability or usefulness of e-commerce website sambal nyoss by using Likert scale. Likert scale serves to determine the scale category from 1 to 5. The methodology in this research is using the waterfall software design methodology. The results of e-commerce web testing on usability testing using the Likert scale method can be concluded that the average Likert Score of the usability test is 4. The value of 4 in the likert scale is the category agreed, so the usability level can be accepted by the user. The test results also mean that web e-commerce samboss nyoss has met usability aspect values such as ease of system, easy to remember system, efficiency, no errors or errors and have a level of user satisfaction